Specific T Cell Responses against Minor Histocompatibility Antigens Cannot Generally Be Explained by Absence of Their Allelic Counterparts on the Cell Surface. Issue 12 (23rd February 2018) - Bijen, Helena M.; Hassan, Chopie; Kester, Michel G. D.; Janssen, George M. C.; Hombrink, Pleun; de Ru, Arnoud H.; Drijfhout, Jan Wouter; Meiring, Hugo D.; de Jong, Ad P.; Falkenburg, J. H. Frederik; Jimenez, Connie R.; Heemskerk, Mirjam H. M.; et al.
Abstract: Allogeneic stem cell transplantation has emerged as immunotherapy in the treatment of a variety of hematological malignancies. Its efficacy depends on induction of graft versus leukemia by donor lymphocytes. Both graft versus leukemia and graft versus host disease are induced by T cells reactive against polymorphic peptides, called minor histocompatibility antigens (MiHA), which differ between patient and donor and are presented in the context of self‐HLA (where HLA is human leukocyte antigen). The allelic counterpart (AC) of the MiHA is generally considered to be absent at the cell surface, based on the absence of immune responses directed against the AC. To study this in detail, we evaluate the recognition, HLA‐binding affinity, and cell surface expression of three selected MiHA. By quantitative MS, we demonstrate the similarly abundant expression of both MiHA and AC at the cell surface. We conclude that the absent recognition of the AC cannot generally be explained by insufficient processing and presentation at the cell surface of the AC.